2007
DOI: 10.1093/ndt/gfl840
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of 'K/DOQI Clinical Practice Guidelines for Bone Metabolism and Disease in Chronic Kidney Disease' after the introduction of cinacalcet in a population of patients on chronic haemodialysis

Abstract: In summary, the combination of cinacalcet and low doses of vitamin D improved significantly the control of PTH and Ca x P in patients with severe secondary hyperparathyroidism on chronic haemodialysis, without adverse effects and with lower doses of phosphate binders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 11 publications
1
51
1
2
Order By: Relevance
“…Prescription patterns for hemodialysis patients with secondary hyperparathyroidism have begun to vary widely since cinacalcet introduction (1)(2)(3), and the effects of these patterns on laboratory values (1-9) and clinical outcomes (10,11) have attracted attention. Before cinacalcet introduction, the only treatment option available for elevated parathyroid hormone (PTH) levels was vitamin D receptor activator (VDRA) (12).…”
Section: Introductionmentioning
confidence: 99%
“…Prescription patterns for hemodialysis patients with secondary hyperparathyroidism have begun to vary widely since cinacalcet introduction (1)(2)(3), and the effects of these patterns on laboratory values (1-9) and clinical outcomes (10,11) have attracted attention. Before cinacalcet introduction, the only treatment option available for elevated parathyroid hormone (PTH) levels was vitamin D receptor activator (VDRA) (12).…”
Section: Introductionmentioning
confidence: 99%
“…The combined results of RCTs and phase 4 studies confirmed these results (11,13,21,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)) (Table1), among other benefits, including a substantial reduction of the elevated bone formation rate/tissue area, generally improving bone disease (57,58). Importantly, two recent prospective RCTs evaluated both the efficacy of cinacalcet in preventing the progression of CV calcifications (ADVANCE) (11), and its effect on clinical outcomes, including all-cause mortality and CV events (EVOLVE) (13).…”
Section: Cinacalcet Use In Patients With Ckd Treated By Dialysismentioning
confidence: 55%
“…29 The consistent achievement of KDOQI goals for bone and mineral metabolism has been difficult with standard therapy, with a large proportion of patients exhibiting persistent and refractory SHPT. [30][31][32][33] Not surprisingly, only about 6.6% and 10.9% of dialysis patients simultaneously met KDOQI targets for PTH, phosphorus, calcium, and calcium-phosphorus product levels in 2003 and 2004, respectively. 32 Presumably, this is related to the fact that attempts to suppress serum PTH with increasing doses of active vitamin D analogues are limited by the development of hypercalcemia and worsening hyperphosphatemia.…”
Section: Safety Profilementioning
confidence: 99%
“…32 Presumably, this is related to the fact that attempts to suppress serum PTH with increasing doses of active vitamin D analogues are limited by the development of hypercalcemia and worsening hyperphosphatemia. 33 The likelihood of developing hypercalcemia with active Vitamin D analogues is further increased by the concomitant use of calcium-containing phosphate binders. In contrast, cinacalcet while suppressing PTH levels simultaneously reduces serum calcium and phosphorus levels thereby adequately controlling not only PTH but also calcium, phosphorus, and calcium-phosphorus product and this effect may be sustained for up to 3 years.…”
Section: Safety Profilementioning
confidence: 99%
See 1 more Smart Citation